A new species of Mammillaria (Cactaceae) from Tamaulipas, México - Martínez-Ávalos, José Guadalupe; Golubov, Jordan; Arias, Salvador; Villarreal-Quintanilla, José Ángel (Instituto de Ecología, A.C., 2011)
Mammillaria cielensis (Cactaceae), a new species of Cactaceae from “El Cielo” Biosphere Reserve (RBC) in Tamaulipas, Mexico, is described and illustrated. The new species is similar to M. zublerae Repp., differing from this species in the size of the stem, the rounded form of the apex, the smaller tubercles, the areoles with white wool, the more numerous and somewhat shorter radial and central spines, the colour and size of the fruits, the shinier and larger seeds, with heavily pitted and slightly reticulate testa, and larger hilum. Its known distribution is restricted to pine oak forest in the RBC, in the southern part of the state of Tamaulipas, Mexico. A comparison with related species is presented.